Optimization of a HPLC procedure for simultaneous determination of cisplatin and the complex cis,cis,trans-diamminedichlorodihydroxoplatinum(IV) in aqueous solutions - Yalexmi Ramos; Carlos Hernández; Lidia Asela Fernandez; Mayra Bataller; Eliet Veliz; Renny Small (Química Nova, 2011)
A RP-HPLC procedure for the simultaneous determination of cisplatin and the complex cis,cis,trans-diamminedichlorodihydroxo-platinum(IV), was development. The developed procedure was validated in terms of linearity, accuracy, precision, limits of detection (LOD), limits of quantification (LOQ) and specificity. The limits of detection (LOD) were 0.47 x 10-4 and 0.53 x 10-4 mol L-1 and the limits of quantification (LOQ) were 1.57 x 10-4 and 1.75 x 10-4 mol L-1, for cisplatin and cis,cis,trans-diamminedichlorodihydroxopla-tinum(IV), respectively. The average recoveries of cisplatin and cis,cis,trans-diamminedichlorodihydroxoplatinum(IV) was 100.6% ± 1.4 and 101.2% ± 1.1, respectively. Intermediate (inter-day) precision, repeatability and specificity of the procedure for hydrolysis products of cisplatin were studied. The results of the study showed that the proposed RP-HPLC procedure is simple, rapid, precise, accurate and specific.